[PP.09.03] PROTEOMIC ANALYSIS OF KIDNEYS FROM SPONTANEOUSLY HYPERTENSIVE AND NORMAL RATS REVEALS CLIC-4, AS A PUTATIVE BIOMARKER IN HYPERTENSIVE NEPHROPATHY. (September 2016) - Hatziioannou, A.; Bakras, G.; Critselis, E.; Zoidakis, J.; Vlachou, A.; Charonis, A.; Vlahakos, D.V.
Abstract : Objective: Hypertensive nephrosclerosis is a major cause of declining kidney function. We aimed to identify novel markers associated with pathogenesis and development of hypertensive nephrosclerosis in experimental animals. Design and method: We compared kidney tissues from spontaneously hypertensive rats (SHR) and Wistar Kyoto normotensive rats (WKY) using comparative proteomic analysis at 6 (development of HTN), 13 (establish HTN), and 20 (beginning of albuminuria) weeks of age. BP was measured in conscious animals using a tail-cuff technique. 2-D Gel Electrophoresis was used to identify stained protein spots differing between hypertensive and normotensive rats. Each spot was excised manually, digested with trypsin and analyzed with a MALDI-TOF/TOF mass spectrometer. The acquired spectra were processed with the Flexanalysis v 2.2 software and protein identification through peptide mass fingerprinting was performed by the use of the MASCOT Server v 2.0. Western blot analysis was used to confirm the proteomic data on differentially expressed proteins in kidneys from SHR. To identify in which specific cell type of renal parenchyma the differences in protein expression occur, we performed immunohistochemical and immunofluorescence studies. Results: The proteomic analysis of SHRs and control kidney tissue yielded a significant number of differentially expressed proteins and altered biological pathways. Overexpression of ClC-4 in SHR kidney tissue is associated with the development of hypertension and establishment of hypertensive nephrosclerosis. Besides its pathogenetic significance, ClC-4 may be a novel diagnostic and therapeutic marker in essential hypertension. Conclusions: The proteomic analysis of SHRs and control kidney tissue yielded a significant number of differentially expressed proteins and altered biological pathways. Overexpression of ClC-4 in SHR kidney tissue is associated with the development of hypertension and establishment of hypertensive nephrosclerosis. Besides its pathogenetic significance, ClC-4 may be a novel diagnostic and therapeutic marker in essential hypertension.